When victims refuse and prosecutors decline: examining exceptional clearance in sexual assault cases - Richards, Tara N. (Crime & delinquency, 2019)
This study examines the predictors of sexual assault case clearance, with a focus on arrest and two types of exceptional clearance: victim refusal to cooperate and prosecutorial declination to prosecute. Using National Incident Based Reporting System (NIBRS) data on crime incidents that contain a sexual offense (N = 21,977), we estimated a multinomial regression model to examine the predictors of different clearance types for cases of sexual assault. Results indicated that the likelihood of victim refusal decreases in cases perpetrated by strangers, involving victim injury, occurring in public, and involving multiple offenses. A similar pattern of findings was observed for the decision to decline to prosecute a case. In addition, prosecutors are more likely to decline to prosecute cases with male victims and older victims. We discuss the implications of our findings and directions for future research.